Сепсис как причина летальных исходов после ампутации нижней конечности на уровне бедра вследствие гангрены у больных синдромом диабетической стопы - Капшитарь, А. В.; Капшитарь, А. А.; Kapshitar, A. V.; Kapshitar, A. A.; Капшитар, Олександр Васильович; Капшитар, Олексій Олександрович (Запорізька медична академія післядипломної освіти МОЗ України, 2019)
Цель исследования. Изучить частоту фатального сепсиса, причины и тяжесть у пациентов сахарным диабетом, осложнённым синдромом диабетической стопы, гангреной конечности, после ампутации нижней конечности на уровне бедра. Материал и методы. Ампутация нижней конечности на уровне бедра выполнена 180 больным синдромом диабетической стопы, гангреной конечности. Умерли 15 (8,3%) пациентов. Результаты. Из 15 умерших больных 9 погибли от сепсиса. Догоспитальный период длился 4–30 суток. В сепсисе госпитализированы 5 и септическом шоке – 4 пациента. Двух- и трёхэтапные операции осуществлены у 5 больных. Им вначале выполнены, «малые» операции. Последующее развитие гангрены стопы и голени завершилось ампутацией нижней конечности. Первичные ампутации выполнены у 4 пациентов. Сепсис явился причиной смерти у 5 больных и сочетание сепсиса с острым или повторным инфарктом миокарда – у 4 больных. На аутопсии выявлены тяжёлые патоморфологические изменения сахарного диабета, осложнённого синдрома диабетической стопы, сепсиса, всех органов и систем. Выводы. Неудовлетворительная организация медицинской помощи пациентам сахарным диабетом и синдромом диабетической стопы на догоспитальном этапе, не эффективная санитарно-просветительная работа, системные патоморфологические изменения привели к сепсису и смерти после ампутации нижней конечности на уровне бедра. Purpose of the study. To study frequency of fatal sepsis, the causes and severity of diabetes patients complicated by diabetic foot syndrome of the gangrene limb, after amputation of the lower limb at the hip level. Material and methods. Amputation of the lower limb at the hip level was performed in 180 patients with diabetic foot, gangrene of the limb. 15 (8,3%) died. Results. From the 15 patients who died, 9 died from sepsis. The age was 54–78 years old. On admission, sepsis was diagnosed in 5 and septic shock – in 4 patients. After examination and preparation, emergency surgeries were performed in 4 patients and urgent surgeries – in 5. Two- and three-step surgeries were performed in 5 patients. They first performed the removal of the toes of the gangrene, osteomyelitis, opened deep phlegmon of the foot and the lower leg was completed by amputation of the lower limb. Primary amputations were performed in 4 patients. Sepsis was the cause of death in 5 patients from 11 to 60 days and the combinations of sepsis with acute myocardial infarction or repeated myocardial infarction – in 4 from 5 to 17 days. During the autopsy, pathological changes of severe diabetes, complicated diabetic foot syndrome, its mixed form, sepsis with manifestations of septicemia or septicopyjemia, and all organs and systems were revealed. Conclusions. The unsatisfactory organization of medical care for patients with diabetes and diabetic foot syndrome at the pre hospital stage, ineffective sanitary and educational work, systemic pathological changes led to sepsis and death after the amputation of the lower limb at the hip level.
Sepsis as a cause of fatal cases after the lower limbs amputation at the hip level due to gangrene in patients with a diabetic foot syndrome
Keywords: сепсис; синдром диабетической стопы; ампутация конечности; летальность; sepsis; diabetic foot syndrome; limb amputation; mortality